(untitled) (Research, Society and Development, 2022)
Objective: To analyze Hospitalizations for Cardiovascular Conditions Sensitive to Primary Health Care in the State of Sergipe in the period 2010 - 2020. Method: This is an ecological study, of time series through the analysis of data from the DATASUS system, with information of hospitalizations carried out by the Authorizations for Hospital Admissions of the Unified Health System, and population data obtained from the Brazilian Institute of Geography and Statistics. Four diseases were considered, namely: Systemic Arterial Hypertension (SAH), Heart Failure (HF), Acute Myocardial Infarction (AMI) and Cerebrovascular Accident (CVA). The annual hospitalization rates were calculated according to the variables cause and Mesoregions. Results: It was possible to notice a decrease in SAH, IC and CVA, when considering the total period studied. Among the diseases analyzed, Heart Failure (HF) was the condition that presented the greatest absolute fall, followed by Cerebrovascular Accident (CVA). Acute myocardial infarction (AMI) showed an increase in the rate, in the total comparison. Conclusion: The results suggest a reduction in the rates of two diseases analyzed and a tendency for the others to remain high. With this result, it is possible to infer that there is a greater need to work on resolutions to reduce risk factors for AMI and CVA, since they involve modifiable risk factors that are more easily dealt with in Primary Health Care. In this sense, measures that work by associating a better control of risk factors and educational measures regarding these diseases may be an interesting suggestion for society, since risk factors may still be unknown.